The Factors Influencing Employee’s Work Performance in Financial Card and Payments Services Industry - Thurga, Velusamy (2018)
The purpose of this study is to examine the factors influencing employee’s work performance in financial card and payments services industry. The factors that were chose for this study are motivation, leadership and working environment. The survey method was used to collect primary data through use of questionnaire to the employees that attached with the financial card and payments services industry. Around 120 set of questionnaires were distributed and 80 set of questionnaires collected from the respondents was used for the analysis of the study. All the data was gathered from the respondents were analyzed using Statistical Package for Social Science (SPSS) software and using the descriptive and inferential statistics. There are various types of data analysis adapted in this research such as reliability analysis, descriptive analysis, correlation analysis and multiple regression analysis. Descriptive analysis technique is used to identify the demographic of respondents in the aspect of gender, age, marital status, race, academic qualification, years of working experience, income group and management level. Furthermore, multiple regression analysis is used to determine the correlation between motivation, leadership and working environment with employee’s work performance in financial card and payments services industry. The result of the study shows that there is a moderate correlation between motivation and working environment towards employee’s work performance. The second factor, leadership has negatively correlated with the employee’s work performance. This study has played an important role to identify the factors influencing employee’s work performance in financial card and payments services industry.